2016
DOI: 10.1039/c6ta07519c
|View full text |Cite
|
Sign up to set email alerts
|

Highly active and stable AuNi dendrites as an electrocatalyst for the oxygen reduction reaction in alkaline media

Abstract: AuNi hierarchical dendrites were fabricated by a facile electrodeposition and dealloying method with exceptional ORR activity and remarkable long-term stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 52 publications
3
34
0
Order By: Relevance
“…Very recently, Au–M (M = Cu, Ni, Co, and Zn) bimetallic nanostructures have garnered intensive interest due to their unique catalytic activity and durability in the electrocatalysis . Especially, AuNi nanostructures exhibit a promising prospect in catalyzing a variety of reactions.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Very recently, Au–M (M = Cu, Ni, Co, and Zn) bimetallic nanostructures have garnered intensive interest due to their unique catalytic activity and durability in the electrocatalysis . Especially, AuNi nanostructures exhibit a promising prospect in catalyzing a variety of reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, AuNi nanostructures exhibit a promising prospect in catalyzing a variety of reactions. [6,12a,13] Our recent study has indicated that the AuNi dendrites by using electrodeposition and additional dealloying process (labeled as AuNi‐DD) showed superior catalytic activity and stability toward ORR compared to the commercial Pt/C. [12a] He et al prepared the carbon supported AuNi nanoparticles by the chemical method, showing that AuNi/C catalyst apparently promoted the electrode kinetics of BH 4 − oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations